2018
DOI: 10.1038/s41598-018-30051-2
|View full text |Cite
|
Sign up to set email alerts
|

Heterotetrameric annexin A2/S100A10 (A2t) is essential for oncogenic human papillomavirus trafficking and capsid disassembly, and protects virions from lysosomal degradation

Abstract: Human papillomavirus (HPV) entry into epithelial cells is independent of canonical endocytic pathways. Upon interaction with host cells, HPV establishes infection by traversing through an endocytic pathway that is clathrin- and caveolin-independent, but dependent on the annexin A2/S100A10 heterotetramer (A2t). We examined the contribution of monomeric annexin A2 (AnxA2) vs. A2t in HPV infection and endocytosis, and further characterized the role of these molecules in protein trafficking. We specifically show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 91 publications
(78 reference statements)
1
45
0
Order By: Relevance
“…Furthermore, increased expression of annexin A2 on the surface of host cells upon exposure to HPV has been reported; annexin A2 forms complex with CD63 and facilitate HPV trafficking. It was further demonstrated that attenuation of annexin A2 may result in an impaired virus internalization, capsid uncoating, and exposed the viral particle to accelerated lysosomal degradation . Taken together this shows that annexin A2 served as an indispensable receptor molecule in HPV infection, involved in virus attachment, internalization, and intracellular trafficking.…”
Section: Role Of Annexin A2 In Virus Interaction With Host Cell Upon mentioning
confidence: 86%
“…Furthermore, increased expression of annexin A2 on the surface of host cells upon exposure to HPV has been reported; annexin A2 forms complex with CD63 and facilitate HPV trafficking. It was further demonstrated that attenuation of annexin A2 may result in an impaired virus internalization, capsid uncoating, and exposed the viral particle to accelerated lysosomal degradation . Taken together this shows that annexin A2 served as an indispensable receptor molecule in HPV infection, involved in virus attachment, internalization, and intracellular trafficking.…”
Section: Role Of Annexin A2 In Virus Interaction With Host Cell Upon mentioning
confidence: 86%
“…To follow HPV16 during the early steps of virus entry, we performed immunofluorescence stainings of the major capsid protein L1 and CD63, a tetraspanin that accumulates with HPV16 capsids in multivesicular bodies (MVBs) [18,45]. As earlier described, control siRNA-treated HeLa cells showed prominent HPV16-CD63 colocalization in vesicular structures (Fig.…”
Section: Post-binding Steps Of Hpv16 Entry Require Cd9mentioning
confidence: 85%
“…We previously reported that this manipulation of LC by HPV is facilitated by the interaction with the annexin A2 S100A10 heterotetramer (A2t) [20]. Further investigation showed that A2t was directly involved in infectious trafficking of HPV virions [21]. In exploring the role of A2t in HPV-LC interactions, we made the interesting observation that BG structures were impacted by modulation of A2t expression, warranting further investigation into the relationship between A2t and BG formation.…”
Section: Introductionmentioning
confidence: 92%